Analysis Of the Implementation of Determination of Usage Status of State-Owned Assets Through Siman Version 2At The Ministry of Public Works - Setyaningsih, Rayi; Ganis Sukoharsono, Eko; Iqbal, Syaiful (The International Journal of Accounting and Business Society, 2025)
Purpose — This paper aims to analyze the implementation of Usage Status Determination of State-Owned Assets (PSP BMN) using the SIMAN Version 2 application at the Ministry of Public Works, as part of Indonesia's digital public sector transformation. The study evaluates this system's effectiveness, challenges, and sustainability dimensions. Design/methodology/approach — Employing a qualitative case study, the research integrates the Technology Acceptance Model (TAM) to assess perceived usefulness, perceived ease of use, user attitudes, behavioral intentions, and actual usage. Data were collected through in-depth interviews and documentation, and the Pentuple Bottom Line sustainability framework was applied for comprehensive evaluation. Findings — SIMAN Version 2 enhances bureaucratic efficiency, transparency, and accountability in asset management. The system also fosters moral responsibility but faces persistent technical and non-technical obstacles, including system stability, data migration, and limited human resources. Integrating both TAM and sustainability frameworks reveals the significance of user acceptance and broader public value. Practical implications — The study highlights the importance of continuous system improvement, user training, and sustainable technology development in public sector digitalization. Integrating technological and value-based approaches is crucial for ethical and practical information system implementation in government asset management. Originality/value — This research applies a multidisciplinary approach by combining TAM and the Pentuple Bottom Line in evaluating a national digital public asset management system. It provides novel insights into technology acceptance, sustainability, and ethical governance practices in Indonesia’s public sector digital transformation.